Hydrophilic PAMAM dendrimer grafted Janus membrane for oil-water emulsion separation - Yunqi Chen; Xiang Wang; Haoyuan Sun; Xinqiang Wang; Baihu Dong; Chaogang Fan; Yingfeng Tu; Shaohui Lin; Qinmin Pan; Xianshe Feng; Flora T.T. Ng (Journal of Environmental Chemical Engineering, 2026)

Experimental study of a dual-chain transmission hybrid power generation wave energy converter - Chenglong Li; Guojun Pan; Hui Li; Beichen Lin; Shaohui Yang; Weiwei Fan; Xianbin Yan (Ocean Engineering, 2026)

Cation dependent dynamics of sequential and cotransport processes of micro-polystyrene and soil colloids in porous media - Qing Lin; Penghui Lin; Fengrui Wang; Haiyan Zhang; Jiaqi Gong; Shuhua Ji; Shaohui Xu; Xilin She (Environmental Research, 2026)

Dynamic structural reconstruction of CuO under reaction conditions enhances photocatalytic activity in C H bond functionalization - Shaohui Zhang; Jia Liu; Yan Pu; Yifang Zhang; Yingcong Wei; Huaxiang Lin; Jinlin Long; Rongjian Sa; Xianzhi Fu; Rusheng Yuan (Chemical Engineering Journal, 2025)

Tailoring flower-like NiCo LDH/MoS2/HPC ternary hierarchical heterostructures electrodes with enhanced energy density for aqueous asymmetric supercapacitor - Shaohui Wang; Lei Wang; Yanfeng Wang; Lin Li; Hua Wang; Tonghua Wang (Journal of Environmental Sciences, 2025)

Temporal trend of cause-specific mortality burden attributable to ambient PM2.5 from different sectors and fuel types across Chinese provinces during 2015–2022 - Jianheng Chen; Dashan Zheng; Wanqi Wen; Laura Wieser; Gregor Kiesewetter; Chongjian Wang; Shaohui Zhang; Hualiang Lin (Environmental Research, 2025)

Influences of sub-zero temperature on dynamic tensile behavior of rhyolite porphyry - Zilong Zhou; Fanjunhui Mo; Xin Cai; Chu Wang; Chunping Lin; Yuanping Lai; Shaohui Tang; Zhongkang Wang (Cold Regions Science and Technology, 2025)

Dead-fallen shrubs exhibit beneficial effects in enhancing soil microbial activity and soil fertility in arid sandy land restoration - Bo Wang; Wangli Liang; Fei Huang; Shaohui Liang; Zhigang Li; Yingge Xie; Gao-Lin Wu (Journal of Environmental Management, 2025)

Boosting the initial Coulombic efficiency of Bi2S3-based anode for practical sodium-ion batteries - Lankun Shi; Rongji Jiao; Dawei Lan; Li Wang; Yu Gao; Meng-Fang Lin; Zhongmin Lang; Wenxiu He; Guixiao Jia; Jinlong Cui; Shaohui Li (Chemical Engineering Journal, 2025)

An Approach to Optimize the Efficiency of an Air Turbine of an Oscillating Water Column Based on Adaptive Model Predictive Control - Yan Huang; Weixun Dong; Jianyu Fan; Shaohui Yang; Zhichang Du; Yongqiang Tu; Chenglong Li; Beichen Lin (Journal of Marine Science and Engineering, 2025)
Wave energy, as a vast renewable resource, remains underutilized despite its high potential. The oscillating water column (OWC) is one of the most efficient way to harvest wave energy. Due to the randomness of ocean wave excitation, a control strategy is needed to keep the conversion efficiency of OWC at a certain level. In this paper, an adaptive model predictive control (AMPC) method is proposed to optimize the efficiency of the air turbine and improve the overall efficiency of the OWC. Experiments were conducted in a wave flume to obtain realistic wave data, which were fed into the AMPC model for simulations. Results indicate that AMPC-optimized turbine efficiency exhibits improved performance under regular wave conditions and significantly enhances efficiency within certain intervals under short-period irregular waves. However, as the wave period increases, optimization becomes less stable. Overall, the study concludes that the adaptive MPC model effectively optimizes turbine efficiency under most conditions, highlighting its potential for enhancing OWC performance.

Insight into shortening mechanisms of start-up time for three-dimensional biofilm electrode reactor/pyrite-autotrophic denitrification coupled system - Xihui Guo; Wentao Zhu; Zhi Wang; Gang Peng; Lin Tan; Tingzhen Ming; Shaohui Zhang; Shiyang Zhang (Bioresource Technology, 2025)

Different co-transport forms of ciprofloxacin with montmorillonite colloids in porous media as affected by pH and cations - Qing Lin; Jiaqi Gong; Xiaowen Liu; Shuhua Ji; Shaohui Xu (Journal of Soils and Sediments, 2024)

Study of a Center Pipe Oscillating Column Wave Energy Converter Combined with a Triboelectric Nanogenerator Device - Yan Huang; Shaohui Yang; Jianyu Fan; Zhichang Du; Beichen Lin; Yongqiang Tu; Lei Pan (Journal of Marine Science and Engineering, 2024)
Wave energy is one of the most widely distributed and abundant energies in the ocean, and its conversion technology has been broadly researched. In this paper, a structure that combines a traditional center pipe oscillating water column and a triboelectric nanogenerator is proposed. Firstly, the structural characteristics and geometric parameters of the device are designed. The working process of the device is introduced, the motion equation of the device is established, and the power generation principle of the triboelectric nanogenerator is deduced and analyzed theoretically. Secondly, hydrodynamic modeling and simulation are carried out, the influence of the bottom shape of the main floating body and the structural parameters of the sag plate on the hydrodynamic force of the device is analyzed, and an electric field simulation of the generation process of the friction nanogenerator is carried out. Finally, experiments involving the wave water tank of the proposed device are conducted, including charging the capacitor of the device under different wave conditions and directly lighting the LED lamp. The performance of the proposed device under different wave conditions is discussed. According to the test results, the feasibility of the proposed device for wave energy conversion is confirmed.

Coupled effects of pH and kaolinite colloids on antibiotic transport in porous media - Shuhua JI; Xiaowen LIU; Xiu MENG; Shaohui XU; Qing LIN (Pedosphere, 2023)

Investigation on dynamic performance of wind turbines using different scaling methods in wind tunnel tests - Kun Lin; Shaohui Xiao; Hongjun Liu; Annan Zhou (Engineering Structures, 2023)

Insights into sorption and leaching behavior of sulfadiazine in soil as affected by humic acid - Qing Lin; Boliang Li; Xiaowen Liu; Budi Zhang; Shaohui Xu (Journal of Soils and Sediments, 2022)

Characterization of a novel echovirus 21 strain isolated from a healthy child in China in 2013 - Hongbo Liu; Shanri Cong; Danhan Xu; Keqin Lin; Xiaoqin Huang; Hao Sun; Zhaoqing Yang; Shaohui Ma (Archives of Virology, 2020)

Impact of heavy metal stresses on the growth and auxin homeostasis of Arabidopsis seedlings - Rui Wang; Jiehua Wang; Lin Zhao; Shaohui Yang; Yingjin Song (BioMetals, 2015)

Variation in Vegetation Structure and Soil Properties, and the Relation Between Understory Plants and Environmental Variables Under Different Phyllostachys pubescens Forests in Southeastern China - Changshun Zhang; Gaodi Xie; Shaohui Fan; Lin Zhen (Environmental Management, 2010)